Csehszlovákia „katonapolitikai" helyzete és az országerődítés 1918-1938 - Suba, János (Közép-Európai Közlemények, 2014)
Building of fortifications after World War I was determined by the general military political situation in Czechoslovakia. The planning and realization of the fortifications need a summary of the military political situation in connection with the development of the armed forces. The ways how the fortifications fit to the defence system require an analysis. The complex military geographical position of the country after 1934 made the fortification work understandable as a reaction to the growing dangers. The basic aim was to fortify the defence capability of the armed forces as well as maintaining the ability to take action as long as the intervention of the allied forces take place. The supreme command of Czechoslovakia could not follow another strategy in the given situation. It was not the strategic planners or the building of the fortifications that resulted in a failure but the improper foreign policy. The strategic situation and its changes obviously influenced the fortification process and its planning, realization and equipment.